2016
DOI: 10.1016/j.athoracsur.2015.09.018
|View full text |Cite
|
Sign up to set email alerts
|

Is Tracheal Transplantation Possible With Cryopreserved Tracheal Allograft and Hyperbaric Oxygen Therapy? An Experimental Study

Abstract: HBOT may be effective in tracheal reconstruction by increasing epithelization and neovascularization after extended tracheal resection. HBOT, therefore, should be considered in CTA transplantation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Patent grafts development and integration after positioning, with also respiratory epithelium recovery, is fundamental to guarantee for a native-like tissue regeneration (instead of reparation) whose functions by far exceed the simple conduction and conditioning of air [ 59 ]. It descends that trachea allograft (or even xenograft) are possibly the most compliant option to resort to, as suggested by derivative’ adequate macroscopic and microscopic anatomy, ECM proteins type/content and ultrastructural organization [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patent grafts development and integration after positioning, with also respiratory epithelium recovery, is fundamental to guarantee for a native-like tissue regeneration (instead of reparation) whose functions by far exceed the simple conduction and conditioning of air [ 59 ]. It descends that trachea allograft (or even xenograft) are possibly the most compliant option to resort to, as suggested by derivative’ adequate macroscopic and microscopic anatomy, ECM proteins type/content and ultrastructural organization [ 60 , 61 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The first preclinical study (pig) reporting about cryopreserved tracheal graft implantation in orthotopic position was described by Lenot et al [ 68 ]. Despite surgery failure due to inadequate blood supply, the histologic structures and the mechanical properties were well preserved, stimulating intense research on this substitute type [ 15 , 24 , 26 , 28 , 38 , 60 , 61 , 67 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Hence, focusing on freezing temperature and liquid nitrogen storage, cryopreserved tracheal graft protocols can be distinguished into two groups: (a) freezing at −60° to −140 °C and storage in liquid nitrogen until use; (b) freezing at −80°/−85 °C, without recurring to liquid nitrogen storage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…The H&E-stained sections were scanned at ×4 magnification, and the area of the obliterated lumen and the total area of lumen were measured using the ImageJ software program (NIH, Bethesda, MD) (Zhao et al, 2013). Histopathologic variables were scored from 0 to 3 to calculate the tracheal necrosis score modified from a method described previously (Iyikesici et al, 2009;Candas et al, 2016) (Supplementary Table S1). Orthotopic explants were dissected latitudinally and longitudinally to examine the anastomosis site stenosis and the viability of the entire explant.…”
Section: Immunohistochemical Analysis Of In Vivo Explantsmentioning
confidence: 99%
“…The beneficial effects of hyperbaric oxygen occur via several mechanisms, including hyperoxygenation, proliferation of fibroblasts, deposition of collagen, angiogenesis, and vasculogenesis. Animal studies of tracheal transplantation have demonstrated several of these mechanisms, including an increase in the number, size, and distance of growth of blood vessels after HBOT (10,11,22,23). HBOT has also been used for the clinical treatment of anastomotic complications related to tracheal resection and reconstruction, where it may help in healing and avoid tracheostomy (13,24,25), and as an adjunctive treatment for POIB in patients with non-small cell lung cancer, where its effects seem to be promising (12,14).…”
Section: A B C D Ementioning
confidence: 99%
“…Their patient showed the first signs of improvement after 27 days of HBOT, which was continued for 40 days with bronchoscopic surveillance. Candas et al reported that HBOT may be effective in tracheal reconstruction by increasing epithelization and neovascularization after extended tracheal resection (23). Ariza-Prota et al also described a patient with complicated tracheal radionecrosis who developed a tracheal ulceration with a small left posterior wall fissure extending into the mediastinum that was successfully treated with HBOT, local debridement, and antibiotics (25).…”
Section: A B C D Ementioning
confidence: 99%